Legal Construction For The Establishment of Land Bank In Land Procurement For Fair Public Interest - Ida Ayu Putu Sri Astiti Padmawati, SH.,MH.; Ida Bagus Sudarma Putra (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
Efforts to build a Land Bank as an institution that assists the government in managing state asset lands should be accompanied by the assignment of appropriate positions, duties and functions to the Land Bank, but the arrangement regarding the position, duties and functions of the Land Bank in the Government Regulation concerning the Land Bank instead reflects the concept the dichotomy that creates a conflict of norms between the private authority of the land bank which is too broad and open through several business activities and cooperation to seek profit as a source of funds which is contrary to the spirit of public service of the Land Bank. The purpose of this study is to examine and describe the urgency of establishing a land bank and the implications of the authority of a land bank in realizing equitable land acquisition for public interests in Indonesia. The results of this study indicate that the urgency of establishing a land bank after the formation of the Law on Job Creation and Government Regulations regarding the Land Bank is because it is driven by Indonesia's urgency over the problem of a very large need for land, which will later be used as a vehicle for investment activities. The implications of the Authority of the Land Bank in the Law on Job Creation and the Government Regulation concerning the Land Bank raises several problems, namely first, the authority overlaps with other land institutions. Second, the strengthening of management rights related to the authority of the land bank is intended as the provision of facilitation and/or licensing services aimed more at increasing investment rather than maximizing the prosperity of the people, this has very broad impacts including 1) Causing an increase in the number of Agrarian Conflicts; 2) Reappearing the principle of Domein Verklaring; 3) Weakening the existence of customary law communities and their customary lands; and 4) Overlapping authorities of land agencies.